Modified Discrepancy Principles with Perturbed Operators and Noisy Data (Journal of Computational Mathematics, 1996)
We investigate a class of a posterior parameter choice for iterated Tikhonov regularization with perturbed operators and noisy data by using modified Arcangeli's method. The rate of convergence of regularization approximation is achieved.